Nobles and nation in Central Europe : free imperial knights in the Age of Revolution, 1750-1850 - Godsey, William D., 1964- (New studies in European history., 2004)
In the late Holy Roman Empire, no group better embodied the traditional noble ideal than the Protestant and Catholic knights in Electoral Mainz. This book traces the transnational 'cultural' landscape in which these knights moved and its transformation by social, political and national revolution in Germany and the Habsburg Empire.